2005
DOI: 10.1071/ea04007
|View full text |Cite
|
Sign up to set email alerts
|

Lamb and sheep meat eating quality — industry and scientific issues and the need for integrated research

Abstract: Abstract. This paper provides an introduction to the special edition of the Australian Journal of Experimental Agriculture dedicated to an integrated research program aimed at understanding the critical control points which determine the consumer defined eating quality of Australian lamb and sheep meat. The reasons for a general approach in the research is outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…However, tenderness alone is not sufficient to explain certain differences attributed by consumers to lamb in this study, because although the meat from Ile de France breed showed a similar shear force to more tender samples in the instrumental evaluation, together with WDB it was one of the least accepted breed types in the sensory evaluation. In this sense, it should be noted that Warner Bratzler shear force measurements are only an estimate of consumer eating quality, without taking into account factors such as taste, juiciness or flavor associated with sheep meats, which is known to be an important component of consumer acceptance …”
Section: Resultsmentioning
confidence: 99%
“…However, tenderness alone is not sufficient to explain certain differences attributed by consumers to lamb in this study, because although the meat from Ile de France breed showed a similar shear force to more tender samples in the instrumental evaluation, together with WDB it was one of the least accepted breed types in the sensory evaluation. In this sense, it should be noted that Warner Bratzler shear force measurements are only an estimate of consumer eating quality, without taking into account factors such as taste, juiciness or flavor associated with sheep meats, which is known to be an important component of consumer acceptance …”
Section: Resultsmentioning
confidence: 99%
“…Due to this, it is crucial to study the acceptability of a product to meet consumer requirements, by obtaining qualitative information, as the Australian Lamb and Sheep meat Industry aims to do (Russell et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…After many years of decline, its production is increasing steadily but its acceptability by a majority of the population is questioned or unknown, in spite of its delicatessen value (Leizaola 2008). Due to this, it is crucial to study the acceptability of a product to meet consumer requirements, by obtaining qualitative information, as the Australian Lamb and Sheep meat Industry aims to do (Russell et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These gains have been driven by genetic improvement flowing from LAMBPLAN and more recently Sheep Genetics Australia . The lamb industry, through research commissioned by Meat and Livestock Australia, has also invested in meat quality research to underpin eating quality of the product (Russell et al 2005). This coordinated approach represents the work of a dynamic industry focussed on the value chain and, most importantly, consumers.…”
Section: Introductionmentioning
confidence: 99%